THE EMERGENCE OF DEATH REPRESENTATIONS IN VISUAL ARTS: STEREOTYPES AND SOCIAL REALITIES - Al-Abbas, Mohammed Baker Mohammed (PEOPLE: International Journal of Social Sciences, 2016)
This article will investigate the impact of Information and Communication Technologies (ICT) on the contemporary practices of today’s artists. Therefore, this investigation will lead to an analogy between the visual representations created by the artist and the representations created by the various forms of ICT. Accordingly, do the artists in this regards critique the stereotypical representations of images or do they copy what they see, the artwork may appear in different visualizations, but the concept is the same. What is the role of the artist in telling the real story behind the fake image created by media? The contemporary artists in some cases created clear distinctions between media and art. The images of death and terror in global media created a strong impact on the global art scene, where some artists copied those images without investigating the real situation on ground. They became another tool controlled by false messages. However, other contemporary artists started to investigate the social reality of media messages and analyse it in their art. Some artists led significant role in criticizing the common stereotypes, which the global media had established in the late few years.